Pemberian PMT Modifikasi Berbasis Kearifan Lokal pada Balita Stunting:: Studi Kasus di Kabupaten Timor Tengah Selatan NTT - Pingge, Yusti Anggi Umbu; Mirasa, Yudied Agung; Winarti, Eko (MES Bogor, 2023)
Stunting is a condition where growth delays occur in children which are characterized by a condition where their bodies are shorter when compared to children of their age. The purpose of this study was to analyze the provision of modified PMT based on local wisdom to stunting toddlers. This research method is the desk study method, namely the collection of data and information including documentation studies and literature studies from the results of previous studies related to this research. Data analysis in this research is content analysis. The results of the study showed that giving modified PMT based on local wisdom to stunting toddlers with the local food type bose corn could improve and increase the nutritional status of children. Provision of additional food ingredients for corn bose can be combined with fish, eggs, nuts, and vegetables to improve children's nutrition. Bose corn can also help increase the productivity of breastfeeding mothers.